1996
DOI: 10.1088/0957-0233/7/10/019
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resolution of a 4-X-wire vorticity probe

Abstract: The spatial resolution of a vorticity probe consisting of four X-wires is studied analytically to evaluate the effects of the separation between different X-wires, the separation between the sensors in each X-wire and the effective angles of the inclined sensors on the statistics of the vorticity fluctuation and its components. Correction ratios for the variance of vorticity and its components as well as their spectra are computed for the case of local isotropy. These ratios are useful for estimating measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…For the present flow conditions, the separation between X-probes in either the z2 or z3 direction is approximately 47/. Our previous spatial resolution analysis of this probe [40] indicated that the high wavenumber part ofvorticity spectra could be attenuated by 70% for i = 2, 3 and 40% for i = 1. The smaller attenuation is r predicted by the analysis is consistent with the smaller discrepancy between the measured and DNS r (Figure 2a).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…For the present flow conditions, the separation between X-probes in either the z2 or z3 direction is approximately 47/. Our previous spatial resolution analysis of this probe [40] indicated that the high wavenumber part ofvorticity spectra could be attenuated by 70% for i = 2, 3 and 40% for i = 1. The smaller attenuation is r predicted by the analysis is consistent with the smaller discrepancy between the measured and DNS r (Figure 2a).…”
Section: Resultsmentioning
confidence: 71%
“…A detailed analysis of the response equation of this probe was given in [40]. The 2.5 #m diameter Wollaston Pt-10% R_h wires were used for all the probes and were etched to an active length of about 0.5 mm.…”
Section: Oui Auimentioning
confidence: 99%
“…The exact and discrete derivatives are used to estimate the error associated with direct calculations of turbulent kinetic energy dissipation. The concept of using a specified turbulent spectrum to estimate bias error and correct measurements lacking sufficient resolution has been applied by others [ Wyngaard , 1968; Zhu and Antonia , 1996; Lavoie et al , 2007]. For the parameters of this experimental setup, direct calculation of the dissipation rate from velocity gradients using the derivative stencil suggested by Raffel et al [1998] and Rosman [2007] underestimates the actual dissipation rate by an order of magnitude for the range of dissipation rates in this study.…”
Section: Methodsmentioning
confidence: 88%
“…The result agrees with previous reports. 18,21 The maxi- mum concentration ofω * z impairs for a larger x/d. Table 2 lists the maximum magnitude ofω * z at x/d = 10, along with previous reports.…”
Section: B Extract Of Coherent Structurementioning
confidence: 99%